Investigation of structural, thermal and dielectric properties of PVC/modified magnetic nanoparticle composites - Tukur, Abdulrahman; Pekdemir, Mustafa Ersin; Coskun, Mehmet (My University, 2020)
Three different composites (5, 10, and 20 wt. %) were prepared using purified PVC and POHg-N3PTMS-g-Fe3O4. Firstly, 3-azidopropyltrimethoxysilane was synthesized under refluxfrom 3-chlorotrimethoxysilane and sodium azide. Then, magnetic nanoparticle was bondedwith the silane group of 3-azidopropyltrimethoxysilane. After that the 3-azidopropyltrimethoxysilane bearing magnetic nanoparticle undergo click reaction withpropargyl alcohol, and then the composites were prepared. Some characterization, includingFT-IR spectroscopy, SEM, Differential scanning calorimetry (DSC), vibrating samplemagnetometer (VSM), and EDX images was performed to the composites. The DSCmeasurements showed that the click reaction of the 3-azidopropyltrimethoxysilane graftmagnetic nanoparticles (N3PTMS-g-Fe3O4) reduced the glass transition temperature (Tg).Click reaction reduced the thermal stability of N3PTMS-g-Fe3O4. The thermal stabilities of thecomposites increased by increasing the compositional rate. It was found that the 10% PVC/POH-g-N3PTMS-g-Fe3O4 reached saturation magnetization (Ms) at 5.12 emu/g. The dielectricconstant (?´) and dielectric loss (? ?) of POH-g-N3PTMS-g-Fe3O4 rapidly decreased withincreasing applied frequency and then remain more or less constant. Also, the AC conductivity(?ac) increased sharply with increasing the applied frequency. While the ?´ decreased slightlyfor the composites by increasing the applied frequency and the ?ac increase dramatically withan increase in applied frequency at room temperature.
Keywords: Malzeme Bilimleri; Özellik ve Test